Kepemimpinan Demokratis Kepala Madrasah Ibtidaiyah (MI) Nurul Ummah Kotagede Yogyakarta - Faiz Auliya Rohman; Nailatul Muna (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2018)
This study discusses the leadership type, style and model of the school principal of an elementary Islamic education institution, Nurul Ummah, Kotagede, Yogyakarta. This research is qualitative in nature, with three data collection techniques: (1) observation, (2) interviews, and (3) documentation. The results of this study indicate that the school principal is discipline, assertive and at the same time democratic. In carrying out his duties and responsibilities, the principal does his best so that the management of the education program in the madrasah goes smoothly as the purpose. The school principal built the basis of the school by setting rules to regulate his subordinate personnel (teachers and staff) to develop and improve the educational aspects, one of which is the preparation of activities in madrasah that have a positive impact on students. The activities that are initiated by the school are: (1) prepare and manage of Madrasah activities programs; (2) improve the quality of education; (3) apply various (new) ideas to develop Madrasah programs; (4) improve the quality of human resources (human resources); (5) behave in discipline and give responsibility in carrying out duties; and (6) active in improving quality and role as a principal. Thus, the principal's leadership becomes a basic value for good change so that madrasas are ready to face all challenges and are able to compete in Islamic education.